Evaluation of Fire Protection System Implementation in A Production Area of Oil and Gas Company, East Java - Pramesti, Devita Aprilia; Ardyanto, Denny; Widajati, Noeroel; Ernawati, Meirina (Jurnal Keselamatan Kesehatan Kerja dan Lingkungan, 2024)
The oil and gas industry is an industry with a high risk of fire. This is because this industry involves several types of substances that cause pressure and have the potential to cause leaks and spills. Industry's inability to detect these conditions can cause fires. Therefore, it is necessary to evaluate the implementation of fire protection systems in the industry. This research was conducted using a checklist method for fulfilling requirements according to appropriate regulations. The results of this assessment show that the company has fulfilled regulations in accordance with each system with a percentage above 75%. Some suggestions that can be considered for improvement include replacing expired fire extinguishers so that they are ready for use, providing APAR signs or symbols at each location point, providing a cover or placing the fire extinguisher outside in a roofed area, equip each hydrant point with instructions for use, carry out hydrant maintenance regarding the completeness and cleanliness of the hydrant box, and update evacuation route signs that are no longer legible and cut trees or branches that cover the signs.